The integration path of mental health education and college students’ ideological and political education - Xu, Li (Hervormde teologiese studies, 2023)
The traditional ideological and political education should keep pace with the times, and the physical and health education should highlight its value, and must combine the two. This study investigated on the integration path of mental health education and college students' ideological and political education. A stratified random sampling was conducted on 2021 students of a higher vocational college. The subjects were divided into the control group and the experimental group. The experimental group was given the integrated intervention course of mental health education and ideological and political education of college students, and the control group was given routine teaching. The depression score of the experimental group is significantly lower than that of the control group, and the mental health quality score is higher than that of the control group. Contribution The integration of mental health education and college students' Ideological and political education can effectively improve the level of college students' mental health. This course constantly improves the students' subjective consciousness, subjective ability and subjective personality, and fully reflects the educational effect of the ideological and political education of college students' mental health course. This research provides data which could be utilised by academics in the field of practical theology, especially youth ministry and religious educational studies.